PERILAKU SAFETY RIDING PENGGUNA SEPEDA MOTOR DI KABUPATEN SUMEDANG BERDASARKAN KARAKTERISTIK PENGGUNA - Fitri Sri Wulandari (Jurnal Kelola: Jurnal Ilmu Sosial, 2022)
Sumedang Regency is one of the regencies in Indonesia that has a fairly high number of motorcycles, with a total of 262,720 motorcycles (BPS 2018). Namely as many as 3 motorcycle users, the number of traffic accidents involving motorcycles is quite high (BPS 2018). With this, a study was conducted that aims to analyze the driving safety behavior of motorcycle users in Sumedang Regency based on demographic characteristics and travel characteristics. The distribution of questionnaires is carried out online through social media to motorcycle users, which will later be used as data to be analyzed. The analysis used is the crosstab method. The attribute that has a relationship with safety riding behavior is the age factor from the characteristics, while the others do not have the characteristics, both from the characteristics and from the characteristics of the trip.